CircRNA circPTK2 Might Suppress Cancer Cell Invasion and Migration of Glioblastoma by Inhibiting miR-23a Maturation - Chen W (Dove Medical Press, 2021)
Wei Chen, Ning Wang, Minxue Lian Department of Neurosurgery, First Affiliated Hospital of Xi’an Jiaotong University, Xi’an City, Shanxi Province, 710061, People’s Republic of ChinaCorrespondence: Minxue LianDepartment of Neurosurgery, First Affiliated Hospital of Xi’an Jiaotong University, No. 277 West Yanta Road, Xi’an City, Shanxi Province, 710061, People’s Republic of ChinaEmail MinxueLianShanxi@163.comBackground: CircRNA circPTK2 plays opposite roles in different cancers, while its role in glioblastoma is unknown. The aim of this study was to explore the involvement of circPTK2 in glioblastoma.Methods: Expression of circPTK2, mature miR-23a, and premature miR-23a in paired cancer and non-cancer tissues from glioblastoma patients (n = 60) was analyzed by RT-qPCR. Pearson’s correlation coefficient was used to analyze the correlations between gene expressions. The effects of circPTK2 overexpression on miR-23a maturation were analyzed by transfecting circPTK2 expression vector into glioblastoma cells, followed by determining the expression of mature miR-23a and premature miR-23a by RT-qPCR. Transwell assays were carried out to explore the role of circPTK2 and miR-23a in regulating glioblastoma cell invasion and migration.Results: We found that circPTK2 was downregulated in GBM and was inversely correlated with mature miR-23a, but not premature miR-23a. GBM cells transfected with circPTK2 expression vector showed significantly downregulated mature miR-23a, but not premature miR-23a. Transwell assay analysis showed that circPTK2 overexpression decreased cell invasion and migration, while miR-23a increased cell invasion and migration. Moreover, miR-23a overexpression reversed the inhibitory effects of circPTK2 overexpression on cell behaviors.Conclusion: CircPTK2 might suppress cancer cell invasion and migration by inhibiting the maturation of miR-23a.Keywords: glioblastoma, circPTK2, miR-23a, maturation, invasion, migration